The Antiphospholipid Syndrome - Fischer, Michael J. (2007)
The antiphospholipid syndrome (APS) is an autoimmune disorder characterized by the clinical association of antiphospholipid autoantibodies (aPL) with a syndrome of hyper-coagulability that can affect any blood vessel, irrespective of type or size. Involvement of larger vessels, such as arteries or veins, manifests in the form of thrombosis or embolism, whereas involvement of smaller vessels, including capillaries, arterioles, and venules, manifests as thrombotic microangiopathy. Virtually any organ in the body, including the kidney, can be affected. Here, we review the basic principles and recent advances in our understanding of APS, and discuss the broad spectrum of renal diseases that have been observed in association with this syndrome. We also discuss the impact that APS may have on pre-existing renal disease as well as current recommendations for treatment of APS.